The Bacillus subtilis rec-assay a powerful tool for the detection of genotoxic substances in the water environment. Prospect for assessing potential impact of pollutants from stabilized wastes - Takigami, H (Waste management (New York, N.Y.), 2002)
The Bacillus subtilis rec-assay has been specially developed to detect genotoxicity in environmental water samples. The rationale of the B. subtilis rec-assay is based on the relative difference of survival of a DNA repair-recombination proficient strain and its deficient strain, which is interpreted as genotoxicity. This assay method can be very powerful in that it has higher sensitivity for the detection of mutagens in highly polluted waters than other bacterial mutation assays. Hydrophobic fractions from various environmental waters were fractionated by using XAD-2 resins and assayed, targeting the detection of organic genotoxic substances. Genotoxic response was detected in most of them, which revealed that many unknown micropollutants with genotoxicity occur in public water bodies. Positive response was also detected from a treated municipal solid waste (MSW) landfill leachate. Genotoxicity remaining in the treated effluent suggests that genotoxic micropollutants may pass through conventional water treatment processes such as activated sludge treatment process. Without proper control of waste quality and landfill facilities, waste landfill could be a heavy pollution source